On Solution and Stability of a Two-Variable Functional Equations - Y. J. Cho; R. Saadati; S. Shabanian; S. M. Vaezpour (Discrete Dynamics in Nature and Society)
The main purpose of this paper is to investigate the stability of the functional equation f(x+y,y+z)=2f(x/2,y/2)+2f(y/2,z/2) in normed spaces. The solutions of such functional equations are considered.